Bangladesh economy 2000 : selected issues - Abdullah, Abu.; Bangladesh Institute of Development Studies (Dhaka : Bangladesh Institute of Development Studies, 2001)
Contributed articles presented at seminar.
Keywords: Bangladesh -- Economic policy; Bangladesh -- Economic conditions